HECS4MQTT: A Multi-Layer Security Framework for Lightweight and Robust Encryption in Healthcare IoT Communications - Saud Alharbi; Wasan Awad; David Bell (Future Internet)
Internet of Things (IoT) technology in healthcare has enabled innovative services that enhance patient monitoring, diagnostics and medical data management. However, securing sensitive health data while maintaining system efficiency of resource-constrained IoT devices remains a critical challenge. This work presents a comprehensive end-to-end IoT security framework for healthcare environments, addressing encryption at two key levels: lightweight encryption at the edge for resource-constrained devices and robust end-to-end encryption when transmitting data to the cloud via MQTT cloud brokers. The proposed system leverages multi-broker MQTT architecture to optimize resource utilization and enhance message reliability. At the edge, lightweight cryptographic techniques ensure low-latency encryption before transmitting data via a secure MQTT broker hosted within the hospital infrastructure. To safeguard data as it moves beyond the hospital to the cloud, stronger end-to-end encryption are applied to ensure end-to-end security, such as AES-256 and TLS 1.3, to ensure confidentiality and resilience over untrusted networks. A proof-of-concept Python 3.10 -based MQTT implementation is developed using open-source technologies. Security and performance evaluations demonstrate the feasibility of the multi-layer encryption approach, effectively balancing computational overhead with data protection. Security and performance evaluations demonstrate that our novel HECS4MQTT (Health Edge Cloud Security for MQTT) framework achieves a unique balance between efficiency and security. Unlike existing solutions that either impose high computational overhead at the edge or rely solely on transport-layer protection, HECS4MQTT introduces a layered encryption strategy that decouples edge and cloud security requirements. This design minimizes processing delays on constrained devices while maintaining strong cryptographic protection when data crosses trust boundaries. The framework also introduces a lightweight bridge component for re-encryption and integrity enforcement, thereby reducing broker compromise risk and supporting compliance with healthcare security regulations. Our HECS4MQTT framework offers a scalable, adaptable, and trust-separated security model, ensuring enhanced confidentiality, integrity, and availability of healthcare data while remaining suitable for deployment in real-world, latency-sensitive, and resource-limited medical environments.